AB0262 Seroconversion and Fluctuation of Current and Novel Biomarkers during Disease Course of RA. (10th June 2014) - De Winter, L.; Hansen, W.; Geusens, P.; Vanhoof, J.; Stinissen, P.; Somers, V.
Abstract : Background: In rheumatoid arthritis (RA), rheumatoid factor (RF) and antibodies against citrullinated proteins (ACPA) are established diagnostic markers. However, up to one third of the RA patients is not detected using these current serological markers. Additionally, no consensus exists concerning the occurrence of seroconversion and the effect of fluctuations in biomarker levels during the course of RA. In a previous study, we identified novel autoantibody biomarkers for RA, and investigated their diagnostic and prognostic value. Two markers, UH-RA.1 and UH-RA.21 were detected in 24% of RA patients. Importantly, both markers were also shown to be present in early and seronegative RA. Objectives: The primary objective of this study was to investigate the variations in levels of the UH-RA antibodies, RF and CCP3 during 18 months in RA patients on a treat-to-target strategy in daily practice. Methods: After screening of 292 RA patients, we selected 50 patients positive for at least one of the two UH-RA markers. The levels of these antibodies were measured at 4 time points with 6-months intervals, together with RF and anti-CCP3 antibodies. A positive status of the UH-RA biomarkers was based on cutoff values defined in our previous study. CCP3 values were classified as negative (<20U), weak positive (20-39U), moderate positive (40-59U) or strong positive (≥60U) according to the manufacturer's guidelines. RF levels above 14U were defined as positive. Results: At baseline, 31/50 (62%) of the RA patients were RF positive and 35/50 (70%) were CCP3 positive. Over the next 18 months, CCP3 serostatus remained unchanged for 38/50 (76%) patients whereas 9/50 (18%) patients changed from negative to positive status. Within this group of nine patients, six patients showed weak positive reactivity, one patient became moderate positive and two patients showed strong positive reactivity. Of the remaining three patients, one patient changed from weak positive to negative while two patients alternated between positive and negative serostatus. The status of RF was retained over time for 45/50 (90%) of patients. Within the other 10% conversions in either direction occurred. The majority of patients with a persistent seropositive CCP3 and RF status showed stable antibody levels. Seroconversion in UH-RA.1 and UH-RA.21 antibody status was more common: 18% and 31% of the RA patients showed a change in serostatus for UH-RA.1 and UH-RA.21, respectively. For UH-RA.1, two patients converted from negative to positive during follow-up. For UH-RA.21, five patients converted from negative to positive, eight patients reverted the other way around. Interestingly, higher fluctuation in antibody levels against UH-RA.1 and UH-RA.21 was observed compared to CCP3 and RF. Conclusions: The levels of RF and anti-CCP3 antibodies remained stable during an 18-month follow-up under standard daily practice therapy. Up to 60% of the CCP3 negative patients converted to a seropositive status within this time frame, indicating the importance of repeated testing of seronegative RA patients. Both seroconversion and fluctuation was more common for the UH-RA biomarkers. Therefore, these novel biomarkers might have prognostic potential for reflecting disease activity. Further analyses will be performed to find possible associations with clinical outcome. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5865